ANALISIS EXPECTATION GAP ANTARA APARAT PENGAWASAN INTERN PEMERINTAH (APIP) DAN PEMANGKU KEPENTINGAN MENGENAI PERAN DAN INDEPENDENSI APIP DALAM PENGAWASAN PENYUSUNAN ANGGARAN BELANJA DAERAH PADA PEMERINTAH PROVINSI SULAWESI UTARA - Singal, Yuanita Iva Maya; Saerang, David Paul E.; Karamoy, Herman (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2016)
As an institution of supervision Inspectorate have a responsibility to review  the drafting of RKA SKPD. In carrying out the functions of supervision, often found the existence of the expectation gap i.e. a difference of wishes or expectations of stakeholders towards the APIP work with the reality of the work shown by the APIP. Expectations of stakeholders sometimes exceeds what the roles and responsibilities of APIP. This research aims to analyze the expectation gap between APIP and stakeholders (auditee) regarding the role and independence of the APIP in supervision of the preparation of the regional budget in the Government of North Sulawesi province. This study used a qualitative approach by taking the location of research in 5 (five) SKPD on the Government of North Sulawesi province with criteria of informant is APIP in North Sulawesi Province of Inspectorate with experience more than 5 (five) years and auditee has the task drafting of RKA. The results of this study showed that at the role of APIP, there is no an  expectation gap but for the issue of perception the limitation of responsibility of APIP, need to be evaluated especially in things still lacking with regards to his responsibilities include improving the quality of human resources such as the understanding of the regulation and its changes and also their skill. Whereas toward independence, on the issue of the perception of the independence of APIP there is no expectation gap but about the influence of the organizational structure of the role and influence of the role of APIP as a consultant found the existence of the expectation gap.   Keywords :  Expectation  Gap, The  Role  Of  APIP, Independence  Of  APIP, Supervision of  The Formation Of The Regional Budget